Clinical features and reclassification of essential tremor with NOTCH2NLC GGC repeat expansions based on a long‐term follow‐up. (25th September 2022) - Zhou, Xun; Huang, Hongyan; He, Runcheng; Zeng, Sheng; Liu, Zhenhua; Xu, Qian; Guo, Jifeng; Yan, Xinxiang; Duan, Ranhui; Li, Jinchen; Tang, Beisha; Xu, Yanming; et al.
Abstract: Background and purpose: NOTCH2NLC GGC repeat expansions have been identified to be associated with essential tremor (ET). Our aim was to characterize ET patients with NOTCH2NLC repeat expansions versus non‐expansions and describe distinctive clinical features of repeat expanded patients with long‐term follow‐up according to the new tremor classification. Methods: Participants included 597 ET pedigrees, 412 sporadic cases and 1085 healthy controls. Repeat expansions of GGC in NOTCH2NLC were screened, and comprehensive clinical features were investigated. A longitudinal clinical assessment and reclassification were performed in NOTCH2NLC expanded patients. Results: In total, 27 ET pedigrees (27/597) and three sporadic patients (3/412) were identified with pathogenic NOTCH2NLC GGC repeat expansions (≥60 repeats). Intermediate‐length GGC repeats (41–59 repeats) were found in four sporadic ET cases and one control subject, and the frequency was higher than that in control participants (4/412 vs. 1/1085, p  = 0.022). About 46 ET patients (43 familial cases from 27 pedigrees and three sporadic cases) with NOTCH2NLC GGC repeat expansions had higher Essential Tremor Rating Assessment Scale I, Essential Tremor Rating Assessment Scale II and Non‐Motor Symptoms Scale scores and lower Mini‐Mental State Examination scores than the patients without expansions. Patients with pathogenic GGC repeats were reclassified as pure ET (25/46), ET‐plus (11/46) and ET‐neuronal intranuclear inclusion disease (10/46) subgroups at 2–8 years of follow‐up. Conclusion: Our results further supported that NOTCH2NLC GGC repeat expansions were associated with ET. Patients with pathogenic GGC repeats presented with more severe motor and non‐motor symptoms. Further long‐term follow‐up and subtype studies will help to define the role of NOTCH2NLC in ET.